Recording of diagnoses in public primary oral health care in a retrospective longitudinal observational study in a Finnish town: Underrepresentation of periodontitis diagnoses - Jouko Kallio; Timo Kauppila; Lasse Suominen; Anna M. Heikkinen (Wiley, 2020)
Abstract Objectives This study investigates which oral diagnoses public primary dental care dentists record. Methods An observational register‐based retrospective follow‐up study was performed in the public primary oral health care of a Finnish town after the dentists were advised to mark the diagnoses in their practices. The rate of recorded diagnoses resulting from visits to the public primary care dentists was studied. The assessed diagnoses were recorded with the 10th revision of the International Classification of Diseases. The distribution of diagnoses was recorded during a 2‐year follow‐up period. Results The most frequent diagnosis groups were dental caries (K02, 38.6%), other diseases of dental hard tissues (K03, 14.9%), diseases of pulp and periapical tissues (K04, 11.4%), periodontal diseases (K05, 9.7%), and different types of bone fractures (S02, 8.1%). Periodontitis was underrepresented. Conclusions In public primary oral health care, there may be difficulties in adequate recording of certain chronic diseases.